Changes in plant species richness following reduced fire frequency and drought in one of the most species‐rich savannas in North America. (19th May 2014) - Palmquist, Kyle A.; Peet, Robert K.; Weakley, Alan S.; Morgan, John
Abstract Questions How has plant species richness changed over two decades in one of the most species‐rich savannas in North America? Is an altered disturbance regime, environmental stress, or both, driving these changes? In what ways can observations in this savanna inform management of other species‐rich plant communities? Location Longleaf pine savannas in southeast North Carolina, USA. Methods In 2011–2013, we re‐surveyed permanent plots established in the 1980s and 1990s in a longleaf pine (Pinus palustris) savanna in North Carolina to quantify changes in species richness at multiple spatial scales following 15 yr of reduced fire frequency plus periodic drought. For comparison, we re‐sampled other longleaf pine savannas in the region that had not experienced reduced fire frequency, but had experienced similar drought. In addition, we identified which types of species were lost and gained, and summarized changes in species frequency by growth form, plant height, and habitat affinity. Results We detected substantial declines in small‐scale species richness and species frequency from the 1980s to 2011, representing a loss of 33% to 41% of the flora, depending on the spatial scale. Small herbaceous species had become particularly scarce. Additional re‐sampling in the wetter years of 2012 and 2013 after consecutive years of fire revealed that species richness had increased slightly from 2011, but was still considerably lower than that in the 1980s. Other savannas did not exhibit such dramatic declines in species richness, suggesting reduced fire frequency in addition to drought contributed to species loss in Big Island Savanna over time. Conclusions Our work suggests that nearly annual fire is necessary for the maintenance of high plant species richness in mesic longleaf pine savannas, and even a modest reduction in fire frequency can have dramatic negative impacts. This study also suggests that drought is an important factor structuring grassland ecosystems in the southeastern US, despite relatively high regional precipitation. We believe these findings can be generalized to other species‐rich grasslands that are sensitive to changes in disturbance regimes and may require frequent disturbance to maintain plant species richness.